Single Parent Nectarinia jugularis - Aida Fithri; Widya Sari (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2018)
Both of Nectarinia jugularis parents, male and female, usually raise their offsprings together. They feed the chicks, carry away faecal sac and keep their offspring safe from any threats such as predators. On one day the female did not appear, it was not clear why she did not come back home. Since then, the male took care of the chicks by feeding them, disposing the faecal sac and keep the chicks save all day, even though he had never slept in the nest at night as the female did. The male tried to increase the feeding rate and faecal sac removal to compensate the absence of the female. Parental care by single parent male continued until they leave the nest. The male still fed the chicks after they flew off from the nest.